LIQUIDITY DETERMINANTS OF SHARIA COMMERCIAL BANKS - asfiyah, lailiyatulmudabbiroh; Dzikrulloh (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2024)
This study aims to analyze the determination of the financing to deposit ratio (FDR), capital adequacy ratio (CAR), and non-performing financing ratio (NPF) on the liquidity of sharia commercial banks from 2018 to 2023. The focus of the sample for this study is sharia commercial banks registered in Financial Services Authority (OJK), through the application of quantitative methodology. This research uses monthly financial reports of Islamic commercial banks from 2018 to 2023 as a sample. The sampling technique applied was purposive sampling, while technical multiple linear regression analysis using SPSS 16.0 was applied to assess the impact of each variable on liquidity. The conclusion obtained from this study states that in that period, NPF had a significant impact on the liquidity of sharia commercial banks. However, apart from that, the FDR and CAR did not show a significant effect on the liquidity of Islamic commercial banks in that period.